Pertumbuhan dan Produksi Genotipe Kedelai (Glycine max L. Merrill) dengan Aplikasi Jenis Mikoriza di Lahan Kering - Widiati, Bibiana Rini; Idrus, Muh. Izzdin; Wahditiya, A. Adriani (Journal Galung Tropika, 2021)
One of the efforts to increase the production of soybean plants in a dry land, which is environmentally friendly with mycorrhizal inoculation, will help absorb water tightly bound to soil micropores and absorb plant nutrients. This research aimed to study the effect of MVA application on increasing the growth and production of soybean genotypes on dry land, determining the type of mycorrhizae that is most compatible with soybean genotypes on dry land, is there an interaction between soybean genotypes and mycorrhizal types so that it is adaptive on dry land. Use Divided plot design (RPT), as follows: Main plot (PU) consists of 6 genotypes of the 4th generation (g) viz : g1 (gM50Gy); g2 (gO50Gy); g3 (gT50Gy); g4 (gM); g5 (gO); g6 (gT). Subplot (AP) is kind mycorrhizae (M), namely control (without mycorrhizae (m0), Glomus etunicatum (m1), Gigaspora margarita, (m2), mixedGlomus etunicatum and the Gigaspora margarita (m3). Each treatment on the main plot and subplots were combined so that there were 24 treatment combinations. The results showed that the soybean genotype was g1 (gM50Gy); g2 (gO50Gy); g3 (gT50Gy) are well adapted to dry land, which is indicated by stomata length and width, higher canopy and root dry weight, and with lower Al uptake. A mycorrhizal application mix Glomus etunicatum and Gigaspora margarita showed the best results on observing length and number of stomata, shoot and root dry weight, root Al uptake, number of filled pods, and seed weight per plot. Treatment (gT50Gy) with mycorrhizal applications mix Glomus etunicatum, and Gigaspora margarita gave the best results on the number of stomata, phosphorus uptake.